Inovasi Video Tutorial Tari Semarang Rumah Kita sebagai Media Pembelajaran Tari Siswa Kelas VIII di SMP N 7 Semarang - Aulia Azka Septyana; Lesa Paranti (Lembaga Pengembangan Kinerja Dosen, 2026)
Dance instruction in schools still does not fully support students' ability to understand techniques and movement sequences independently. In the